Effects of natural antioxidant (vitamin E) on protein kinase C activity in cultured smooth muscle cells. - Ho, Chuong Thanh. (University of Ottawa (Canada), 1993)
Since $\alpha$-tocopherol, the active form of vitamin E, is an integral component of plasma membranes, the possibility that it may affect the activity of membrane-associated enzymes such as protein kinase C (PKC) is being investigated by a number of laboratories. In the present study, we examined the effects of vitamin E and another antioxidant, vitamin C, on PKC activity in A10 cells, an established smooth muscle cell line. Because several lines of evidence have suggested a possible involvement of oxygen free radicals in the activation of PKC, we attempted to elucidate the mechanism(s) by which vitamin E can influence PKC activity. To study the incorporation of vitamin E into A10 smooth muscle cells, cells have been treated with vitamin E-enriched medium for various times and at different concentrations; the results showed that cellular incorporation of vitamin E was increased in a time and dose-dependent manner. The incorporation of vitamin E did not show any effect on A10 cell number whereas it significantly diminished PKC activity in the membrane fraction. To investigate whether this decrease in membrane PKC activity was due to the effect of vitamin E on PKC translocation from cytosol to membrane, western immunoblotting was performed. The result showed that vitamin E treatment did not affect PKC translocation in our system.
Keywords: Chemistry, Biochemistry.